An LC-MS/MS Bioanalytical Assay for the Determination of Gilteritinib in Rat Plasma and Application to a Drug–Drug Interaction Study - Wang Q; Chen Z; Chen D; Ye X (Dove Medical Press, 2020)
Qiong Wang,1 Zhe Chen,1 Dingwen Chen,1 Xia-yan Ye2 1Department of Pharmacy, Wenzhou People’s Hospital, Wenzhou, Zhejiang 325000, People’s Republic of China; 2Department of Brain Surgery, The People’s Hospital of Lishui, Lishui, Zhejiang 323000, People’s Republic of ChinaCorrespondence: Xia-yan YeThe People’s Hospital of Lishui, No.15 Dazhong street, Liandu District, Lishui, Zhejiang, People’s Republic of ChinaEmail 18957093763@163.comBackground: Gilteritinib, a novel, potent FLT3/AXL inhibitor, was recently approved in Japan and USA for the treatment of adult patients who have relapsed or refractory acute myeloid leukemia (AML) with a FLT3 mutation.Purpose and Methods: In this study, we aimed to develop and validate a sensitive and simple ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for the quantification of gilteritinib in plasma and to investigate whether CYP3A4 inhibitors (fluconazole and itraconazole) could influence the pharmacokinetics of gilteritinib from a drug–drug interaction study in rats. Sample preparation was done by a simple protein crash with acetonitrile containing the internal standard (IS) pirfenidone, followed by UPLC-MS/MS quantification.Results: The assay was successfully validated in a 1– 500 ng/mL calibration range for gilteritinib, where the lower limit of quantification (LLOQ) was set at 1 ng/mL. The intra-day and inter-day precisions for gilteritinib were less than 10.6%, and the accuracies were in the range of − 14.5% to 11.1%. Recovery and matrix effect of the analyte and IS were acceptable, and the analyte was stable during the assay and storage in plasma samples. The validated UPLC-MS/MS method was successfully applied to a drug–drug interaction study between gilteritinib and CYP3A4 inhibitors (fluconazole and itraconazole) in rats. Itraconazole significantly increased the exposure of gilteritinib, and affected the pharmacokinetics of gilteritinib in rats, not fluconazole.Conclusion: A further clinical study should be conducted to investigate the effect of itraconazole on the metabolism of gilteritinib in subjects.Keywords: gilteritinib, drug–drug interaction, pharmacokinetic, UPLC-MS/MS, CYP3A4 inhibitors